2011
DOI: 10.1016/j.amjmed.2010.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Marked Reduction in 30-Day Mortality Among Elderly Patients with Community-acquired Pneumonia

Abstract: BACKGROUND-Community-acquired pneumonia is the most common infectious cause of death in the United States. Over the last two decades, patient characteristics and clinical care have changed. To understand the impact of these changes, we quantified incidence and mortality trends among elderly adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 35 publications
6
53
0
4
Order By: Relevance
“…Additionally, several county governments have provided free influenza vaccines to all the county's elderly population and pneumococcal vaccinations to all the county's older elderly (age 75 and older) since 2000 33,34 . Other studies have also shown declining mortality rates among patients with pneumonia over the past 10-20 years 17,35 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, several county governments have provided free influenza vaccines to all the county's elderly population and pneumococcal vaccinations to all the county's older elderly (age 75 and older) since 2000 33,34 . Other studies have also shown declining mortality rates among patients with pneumonia over the past 10-20 years 17,35 .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, we found that mortality gaps between elderly and young patients narrowed over time; namely, the decline in the mortality rate among elderly patients was faster than that among young patients. It is probable that influenza and pneumococcal vaccination rates among elderly patients increased over time because of gradual implementation of government-sponsored vaccination programs for the elderly 17,[32][33][34] . In 1998, a national government-sponsored influenza vaccination program for the elderly (age 65 and older) was introduced in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports have found that pneumococcal and influenza vaccination were associated with reductions in mortality and hospitalizations in patients with CAP. [23][24][25] Offering both pneumococcal and influenza vaccination to the elderly can improve 30-day mortality in patients with CAP. The severity and extension of pneumonia, an inadequate response to infection, and low functional status were the main factors associated with mortality in elderly patients with CAP.…”
Section: Discussionmentioning
confidence: 99%
“…All statistical tests were 2-tailed and statistical significance was established as p value <0.05. The statistical analysis was made using the SPSS v. 23 …”
Section: Methodsmentioning
confidence: 99%